Case report: Dynamic 18F-FDG PET/CT display of a bronchial mass as a second primary cancer mimicking mediastinal lymph node in a gastric carcinoma survivor - Huang, Shengyun; Zhang, Yarong; Wumener, Xieraili; Lei, Yuanyuan (Frontiers in Oncology, 2024)
A 70-year-old woman underwent distal gastrectomy due to gastric adenocarcinoma in 2015. After 6 years, the follow-up CT revealed a suspicious mass in the right hilar of the lung mimicking mediastinal lymph nodes. Further dynamic PET/CT images showed a mass located in the right intermediate bronchus with increased FDG uptake and relatively high Ki value, which may imply the possibility of malignancy. However, the symmetrical mediastinal lymph nodes had intense FDG uptake but relatively low Ki value, suggesting benign lesions. The initial pathological result of the bronchoscopy biopsy was considered suspicious for metastatic gastric adenocarcinoma. However, it was then found consistent with middle-grade mucoepidermoid carcinoma, considered a second primary cancer without metastatic lymph nodes as confirmed by a surgical procedure (lower bilobectomy + hilar and mediastinal lymphadenectomy). 18F-FDG PET/CT has an important value in the follow-up of indeterminate findings for patients with a tumor history. Moreover, dynamic quantification parameters such as Ki may be additionally helpful in identifying malignancies in some equivocal situations.